Siyasal Gelişme Perspektifinin Bir Analizi - Fatma AKKAN GÜNGÖR (Gazi Akademik Bakış)
In terms of the evolution of political development to democratization, many topics are considered to be important in the comparative politics literature. These include: income and democracy, political institutions and comparative development, constitutional design and democracy, political culture, political participation and level of economic development. In this regard, priority should be given to identifying the necessary elements, which help understand the concept of political development, rather than trying to define the concept. Therefore giving definitions of political development should be avoided and topics regarding political development should focus more on content.